2020
DOI: 10.1002/jcp.29623
|View full text |Cite
|
Sign up to set email alerts
|

A mutation in the Na‐K‐2Cl cotransporter‐1 leads to changes in cellular metabolism

Abstract: The Na-K-Cl cotransporter-1 (NKCC1), by mediating the electroneutral transport of Na + , K + , and Cl − plays an important role in cell volume regulation, epithelial transport, and the control of neuronal excitability. Recently, we reported the first known human mutation in SLC12A2, the gene encoding NKCC1. The 17-year old patient suffers from multiorgan failure. Laboratory tests conducted on muscle and liver biopsies of the patient showed abnormal increase in mitochondrial DNA copy number and increased glycog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…Increased activation of the nutrient/energy sensor, mTORC1 is consistent with the increased need for mitochondrial respiration that we observed in cells isolated from the NKCC1-DFX patient and in cells from mice expressing the same mutant transporter (Omer et al, 2020). If NKCC1 functions as a break to the amino acid transporter LAT1 and to the insulin receptor, in macrophages, it also provides a break to the function of phagocytosis (Perry et al, 2019).…”
Section: Na + /Glucose Transporter (Sglt)supporting
confidence: 80%
See 1 more Smart Citation
“…Increased activation of the nutrient/energy sensor, mTORC1 is consistent with the increased need for mitochondrial respiration that we observed in cells isolated from the NKCC1-DFX patient and in cells from mice expressing the same mutant transporter (Omer et al, 2020). If NKCC1 functions as a break to the amino acid transporter LAT1 and to the insulin receptor, in macrophages, it also provides a break to the function of phagocytosis (Perry et al, 2019).…”
Section: Na + /Glucose Transporter (Sglt)supporting
confidence: 80%
“…The mouse exhibited mis-trafficking of the cotransporter to the apical membrane of epithelial cells, decreased intestinal function due to deficit in luminal hydration, deficit in release and expansion of mucus layers (Koumangoye et al, 2020). As surprising, was our demonstration that cells from the mouse had increased mitochondrial respiration, and signs of starvation (Omer et al, 2020).…”
Section: Na + /Glucose Transporter (Sglt)mentioning
confidence: 62%
“…Remarkably, fibroblasts isolated from NKCC1 knockout mice also displayed significant increases in ROS, as established through increase in hydrogen peroxide production and peroxidase activity. 89 These data indicate that the phagocyte phenotype switch might be extendable to other cell types.…”
Section: Nkcc1-dfx Mouse Modelmentioning
confidence: 86%
“…Yet, when the patient fibroblasts were used to measure mitochondrial respiration, the rate of oxygen consumption was significantly higher in the patient fibroblasts, compared to fibroblasts isolated from healthy controls. 89 …”
Section: Patient With a C-terminal Deletion In Nkcc1mentioning
confidence: 99%
“…5k Our findings raise several interesting questions. For instance, previous studies suggest that macropinocytosis facilitates nutrient uptake 64 , and a recent report found that mutation of SLC12A2, a chloride transporter regulated by WNK1, causes altered cellular metabolism 65 . Does WNK1 regulate cellular metabolism downstream of macropinocytosis?…”
Section: Chloride Sensing Via Wnk1 Functions Downstream Of M-csf-indu...mentioning
confidence: 99%